Sexuality in Ultra-High Risk for Psychosis and First-Episode Psychosis. A Systematic Review of Literature - Ciocca, Giacomo; Jannini, Tommaso B.; Ribolsi, Michele; Rossi, Rodolfo; Niolu, Cinzia; Siracusano, Alberto; Jannini, Emmanuele A.; Di Lorenzo, Giorgio (Frontiers in Psychiatry, 2021)
A considerable body of literature reports that individuals with psychotic disorders often suffer from sexual dysfunctions (SDs), with these representing a major unmet need. Long-term antipsychotic drug treatment may be the main cause for SDs in psychotic patients’ SD, through a plethora of different mechanisms, including prolactin dyscrasia, histamine-mediated sedation, and serotonin-induced sexual demotivation. However, a few pieces of evidence treat sexuality in patients at risk or the onset of psychosis. For this purpose, we performed a systematically reviewed of literature ofn the last ten years in order to investigate sexuality in ultra-high risk (UHR) for psychosis (UHR) and first-episode psychosis (FEP). We included in our review 34 articles fitting our research criteria on SDs in UHR and FEP. Evidence of SDs in the transition from UHR to FEP emerges through the selected studies. In FEP, sexuality is affected by the severity of the psychotic symptoms and, in some cases, by the iatrogenic effects of psychopharmacological treatment. Further experimental and clinical studies should systematically investigate the role of sexual functioning in the transition from UHR to FEP and, consequentlythus, clarify whether or notif SDs could be considered a possible marker for the onset of psychosis in at-risk populations. Moreover, psychiatrists and clinical psychologists should take into consideration the role of sexual life in young people with prodromal mental symptoms or at the onset of psychosis. Focusing on a thorough sexual evaluation might be a major challenge that could break down barriers of mental health promotion among young people with schizophrenia-spectrum disorders and therefore achieve better clinical outcomes.